Live literature in the Philippines: an ethnographic study of #RomanceClass and reading as performance. Issue 1 (2nd January 2023) - Parnell, Claire; Trinidad, Andrea Anne; McAlister, Jodi
Abstract: Live literature – events where literature is the dominant art form presented or performed – is a highly visible form of contemporary book culture. In this article, we examine the live reading events organised by #RomanceClass in the Philippines as a case study, using a digital ethnography method which draws on fieldnotes, interviews, social media content, a decibel reader, and a bingo card; and grapple with some of the methodological challenges of researching post-digital literary events. By doing so, we seek not only to explore these fascinating live reading events as specific local phenomena, but also the ways in which the characteristics of a given genre world shape the phenomenology of live literature events more broadly.